PERFORMANCE APPRAISAL AS A MOTIVATIONAL TOOL IN THE PORTUGUESE PUBLIC ADMINISTRATION - Lira, Miguel (2016)
Considering that the Integrated System of Performance Management and Appraisal in the Public Sector (SIADAP) is a performance management tool – of the Portuguese public administration – that is yet barely explored by literature regarding its motivational effects, it is critical to obtain a better understanding of those effects.So as to improve such knowledge, we have carried out an empirical study on SIADAP. The study focused on the civil servants assigned to three institutions, subject to performance appraisal through SIADAP; and it was based on a questionnaire that generated 334 valid responses, which were subjected to a statistical analysis of a descriptive and inferential nature.The study concluded that SIADAP may be an important motivational tool, provided that the appraisees perceive it as an accurate and fair system, and are satisfied with it. However, the study also concluded that the keynote is that respondents consider this system as inaccurate, unfair and are unsatisfied with it. Therefore, the study suggests that SIADAP has a small role in motivating the Portuguese civil servants to improve their performance.